2012
DOI: 10.1002/ajhb.22212
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between breast size and anthropometric characteristics

Abstract: Smaller and larger breasted women demonstrate differences in anthropometry, with body mass and BMI demonstrating strong relationships to breast mass. Measures of BMI and suprasternal notch to nipple distance enable predictions of breast mass and suggest that weight-related parameters are not appropriate exclusion criteria for mammaplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 44 publications
7
29
2
Order By: Relevance
“…It has been reported that the mass of a non-lactating breast ranges from 150 to 225 g (Macéa & Fregnani, 2006), and differences in breast sizes are usually attributed to variations in adipose tissue, which may be representative of different breast masses (Page & Steele, 1999). The mass of the breast has also been shown to be related to the suprasternal notch to nipple distance, with increases in breast mass being associated with inferior migration of the nipple during static conditions (Brown et al, 2012). During dynamic movements, the motion of the soft tissue of the breast is governed by the driving force of the trunk (Haake & Scurr, 2010), the viscoelastic properties of the breast tissue (Gefen & Dilmoney, 2007) and any external breast support garment being worn (Singha, 2012;Zhou, Yu, & Ng, 2012a).…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that the mass of a non-lactating breast ranges from 150 to 225 g (Macéa & Fregnani, 2006), and differences in breast sizes are usually attributed to variations in adipose tissue, which may be representative of different breast masses (Page & Steele, 1999). The mass of the breast has also been shown to be related to the suprasternal notch to nipple distance, with increases in breast mass being associated with inferior migration of the nipple during static conditions (Brown et al, 2012). During dynamic movements, the motion of the soft tissue of the breast is governed by the driving force of the trunk (Haake & Scurr, 2010), the viscoelastic properties of the breast tissue (Gefen & Dilmoney, 2007) and any external breast support garment being worn (Singha, 2012;Zhou, Yu, & Ng, 2012a).…”
Section: Introductionmentioning
confidence: 95%
“…Historically, shape changes have been quantified using traditional one-dimensional (1D) anthropometric measurements such as lengths, breadths, and girths. 1D measurements are used for body shape analysis for various applications including ergonomics (Park and Park, 2013), modeling and design (Behara and Das, 2011;Hawes et al, 1994), biological and evolutionary anthropology (Katzmarzyk and Leonard, 1998;Ruff, 2002), and for health assessments and determining the risk of disease (Brown et al, 2012;Fujimoto et al, 2007;Garlie et al, 2010;Schernhammer et al, 2007;Wells et al, 2010). Multidimensional measurements have largely been examined through simple 1D measures, for example, body volume being calculated using waist circumference and BMI (Heymsfield et al, 2008).…”
mentioning
confidence: 99%
“…Rather, breast size may also act as a cue of nulliparity, age, sexual maturity, or fertility [14][17] and, furthermore, there may be other more important cues of fat storage compared to the breasts, such as overall body size [57], [59]. This may help to explain the small-to-moderate effect sizes uncovered in both studies reported here: all things being equal breast size may indicate fat reserves, but in reality breast size is likely correlated with body mass [72], which may act as a more reliable indicator of such reserves. Determining the relative importance of breast size and body size, respectively, as cues of fat reserves will require further research.…”
Section: Discussionmentioning
confidence: 75%
“…It has been argued, for example, that breasts are one of the most important sites of objectification of the female body in socioeconomically developed settings [4], [72][73] and media targeted at some men appear to fetishise large breasts [74]–[75]. As an aside, this should not be used to suggest that the importance of breasts varies across cultures and that our methodology artificially inflates the importance of breast size: earlier ethnographic research indicates that breasts are eroticised in many different cultures [76].…”
Section: Discussionmentioning
confidence: 99%